2019
DOI: 10.7150/jca.32500
|View full text |Cite
|
Sign up to set email alerts
|

Plan quality comparison for cervical carcinoma treated with Halcyon and Trilogy intensity-modulated radiotherapy

Abstract: Purpose: Varian Halcyon is a novel machine with dual-layer leaves, single flattening filter free (FFF) energy and an enclosed bore. The purpose of this study was to compare the differences in dosimetry and plan parameters of intensity-modulated radiation therapy (IMRT) plans between the Halcyon and Trilogy accelerators. Methods and Materials: A total of 30 IMRT plans from cervical carcinoma patients were retrospectively analyzed on the Trilogy and Eclipse v13.5 treatment planning systems (TPSs). For each patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…Previous studies have demonstrated that Halcyon could reduce the treatment time signi cantly compared to conventional LINACs [3][4][5][6][7]. Our study proved the same results in radiotherapy for bilateral breast cancer.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous studies have demonstrated that Halcyon could reduce the treatment time signi cantly compared to conventional LINACs [3][4][5][6][7]. Our study proved the same results in radiotherapy for bilateral breast cancer.…”
Section: Discussionsupporting
confidence: 83%
“…Halcyon has many differences from conventional C-arm LINACs, such as jawless, dual-layer multi-leaf collimator (MLC), faster gantry rotation and daily image guided radiotherapy (IGRT). Comparable dose distribution and excellent delivery e ciency have been shown on Halcyon in radiotherapy for head and neck, brain, unilateral breast, and cervical cancers [3][4][5][6][7]. Trilogy is a conventional C-arm LINAC with jaw and Millennium MLC.…”
Section: Introductionmentioning
confidence: 99%
“…The potential of Halcyon for cervix uteri was investigated also by Li [20], over a group of 30 patients with a dose prescription of 50.4Gy and no SIB and with dose-volume aims different from the highly demanding Embrace constraints, i.e. in a substantially different setting from what applied in the present investigation.…”
Section: Discussionmentioning
confidence: 92%
“…After its clinical introduction in 2017, the performance of the new radiotherapy delivery platform Halcyon (H, Varian Medical Systems, Palo Alto, USA) was investigated for a variety of different treatment indications [10][11][12][13][14][15][16][17][18][19][20]. In general, the potential performance equivalence between H and other carm delivery systems was proven for head and neck, breast, prostate [13] and brain tumours [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation